Twelve tips for learners to succeed in a CBME program. (3rd July 2021) - Hall, Jena; Oswald, Anna; Hauer, Karen E.; Hall, Andrew K.; Englander, Robert; Cheung, Warren J.
Abstract: The international movement to competency-based medical education (CBME) marks a major transition in medical education that requires a shift in educators' and learners' approach to clinical experiences, the way assessment data are collected and integrated, and in learners' mindsets. Learners entering a CBME curriculum must actively drive their learning experiences and education goals. For some, this expectation may be a significant change from their previous approach to learning in medicine. This paper highlights 12 tips to help learners succeed within a CBME model.